Computing task allocation for power Internet of Things including renewable energy sources - Yang, Xianfei; Yu, Xiang; Li, Xiang (Frontiers in Energy Research, 2024)
Power Internet of Things (PIoT) is the key technology to build a new power system based on new energy. Focusing on the problem that the large amount of data leads to the long computation delay of cloud computing in the operation control process of PIoT including renewable energy sources, this paper establishes a cloud-edge-end collaborative optimization calculation model for PIoT based on edge computation. Combined with data collected by a variety of smart terminal devices (STDs) arranged around the power generation equipment, the edge computation framework of PIoT is analyzed, and a computing task allocation model based on minimizing average system latency is established. The corresponding simulation model is built for simulation verification. Compared with other baseline schemes, it has been demonstrated that the average system latency of all tasks can be significantly decreased by using the proposed optimization scheme.